Negotiating the Fabric of the African University : Volume 1 - Global Narratives and Local Models - Kaldewey, David,; Langa, Patrício, (African Higher Education: Developments and Perspectives ;, 2025)
This book is the first volume of two edited collections that critically assess the historical and contemporary processes that have shaped the formation and transformation of the African university. It provides general perspectives, reflections, and a selection of case studies from different regions and higher education systems, highlighting the vibrant debates on the social and institutional life of universities in Africa. The chapters assembled here capture the rich experiences, strategies, and analyses of students, lecturers, researchers, and administrators, showcasing the university as a dynamic lived experience. Contributors are: Kasturi Behari-Leak, Eli Bitzer, Destin Feutseu Dassi, David Kaldewey, Patrício V. Langa, Laetus O.K. Lategan, Elisio Macamo, Teboho Moja, Mariah Mosomi, Bakheit Mohammed Nur, Lerato Posholi, Leonie Schoelen and Cecilé Swart.